2014
DOI: 10.1007/s13744-014-0208-y
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Distribution of Sensilla on the Antennae of Hylamorpha elegans Burmeister (Coleoptera: Scarabaeidae)

Abstract: Considering that sensilla constitute important functional elements of sensory systems in insects, the aim of this study was to determine the type and distribution of sensilla in the antennae of Hylamorpha elegans Burmeister examined by scanning electron microscopy. Hylamorpha elegans antennae are lamellate and consist of the scape, pedicel, and flagellum. The antennal club of this beetle consists of three terminal plates: proximal, middle, and distal lamellae. Four types of sensilla were observed in the lamell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…In most scarab beetles, as in the generality of insects, sex pheromones are released by the females to attract males, and therefore the number of pheromone‐sensitive sensilla (placodea, in case of scarab beetles) is much greater in males (Kim and Leal, ; Leal, ). A similar sexual dimorphism seems to be a rule in Rutelini (Ågren, ; Kim and Leal, ; Mutis et al, ) and Melolonthini (Allsopp, ; Romero‐López et al, ) (Table ), but is not observed in O. eremita . Different density and distribution of olfactory sensilla in various species may reflect different ways in the use of sexual pheromones for intraspecific communication.…”
Section: Discussionmentioning
confidence: 83%
“…In most scarab beetles, as in the generality of insects, sex pheromones are released by the females to attract males, and therefore the number of pheromone‐sensitive sensilla (placodea, in case of scarab beetles) is much greater in males (Kim and Leal, ; Leal, ). A similar sexual dimorphism seems to be a rule in Rutelini (Ågren, ; Kim and Leal, ; Mutis et al, ) and Melolonthini (Allsopp, ; Romero‐López et al, ) (Table ), but is not observed in O. eremita . Different density and distribution of olfactory sensilla in various species may reflect different ways in the use of sexual pheromones for intraspecific communication.…”
Section: Discussionmentioning
confidence: 83%
“…Subsequently, a lateral lamella was excised in order to expose one side of the middle lamella, where olfactory sensilla are located (Mutis et al . ). Signals from antennae were conducted and recorded by Syntech equipment (Kirchzarten, Germany).…”
Section: Methodsmentioning
confidence: 97%
“…A recent study on morphology and distribution of sensilla suggests that males of H. elegans have more chemosensory sensilla than females because males are able to find and recognize females while they are feeding on leaves of N. obliqua (Mutis et al . ). Another special behavior has been highlighted for this beetle: after copulation females fly to crops such as red clover, Trifolium pratense , to deposit their fertilized eggs (Artigas ).…”
Section: Introductionmentioning
confidence: 97%
“…Chemical perception in insects relies on olfaction and gustation, which enable insects to accomplish important tasks such as mating, host finding and predator avoidance in their environment (Sánchez-Gracia, Vieira & Rozas, 2009). Physically, these abilities depend on small, specialized organs called sensilla (Mutis et al, 2014), which populate insect’s appendices, such as antennae and palps. Sensilla are exposed to chemical stimuli and protect the neuronal dendrites inside (Suh, Bohbot & Zwiebel, 2014).…”
Section: Introductionmentioning
confidence: 99%